Sepsis-Induced Myopathy and Gut Microbiome Dysbiosis: Mechanistic Links and Therapeutic Targets. Issue 1 (11th January 2022) - Mankowski, Robert T.; Laitano, Orlando; Darden, Dijoia; Kelly, Lauren; Munley, Jennifer; Loftus, Tyler J.; Mohr, Alicia M.; Efron, Philip A.; Thomas, Ryan M.
Abstract : ABSTRACT: Sepsis is currently defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. The skeletal muscle system is among the host organ systems compromised by sepsis. The resulting neuromuscular dysfunction and impaired regenerative capacity defines sepsis-induced myopathy and manifests as atrophy, loss of strength, and hindered regeneration after injury. These outcomes delay recovery from critical illness and confer increased vulnerability to morbidity and mortality. The mechanisms underlying sepsis-induced myopathy, including the potential contribution of peripheral organs, remain largely unexplored. The gut microbiome is an immunological and homeostatic entity that interacts with and controls end-organ function, including the skeletal muscle system. Sepsis induces alterations in the gut microbiota composition, which is globally termed a state of "dysbiosis" for the host compared to baseline microbiota composition. In this review, we critically evaluate existing evidence and potential mechanisms linking sepsis-induced myopathy with gut microbiota dysbiosis.